Decellularized Human Liver Is Too Heterogeneous for Designing a Generic Extracellular Matrix Mimic Hepatic Scaffold. Issue 12 (23rd May 2017) - Mattei, Giorgio; Magliaro, Chiara; Pirone, Andrea; Ahluwalia, Arti
Abstract: Decellularized human livers are considered the perfect extracellular matrix (ECM) surrogate because both three‐dimensional architecture and biological features of the hepatic microenvironment are thought to be preserved. However, donor human livers are in chronically short supply, both for transplantation or as decellularized scaffolds, and will become even scarcer as life expectancy increases. It is hence of interest to determine the structural and biochemical properties of human hepatic ECM to derive design criteria for engineering biomimetic scaffolds. The intention of this work was to obtain quantitative design specifications for fabricating scaffolds for hepatic tissue engineering using human livers as a template. To this end, hepatic samples from five patients scheduled for hepatic resection were decellularized using a protocol shown to reproducibly conserve matrix composition and microstructure in porcine livers. The decellularization outcome was evaluated through histological and quantitative image analyses to evaluate cell removal, protein, and glycosaminoglycan content per unit area. Applying the same decellularization protocol to human liver samples obtained from five different patients yielded five different outcomes. Only one liver out of five was completely decellularized, while the other four showed different levels of remaining cells and matrix. Moreover, protein and glycosaminoglycan content per unit area after decellularization were also found to be patient‐ (or donor‐) dependent. This donor‐to‐donor variability of human livers thus precludes their use as templates for engineering a generic "one‐size fits all" ECM‐mimic hepatic scaffold.